Developing Industry-Oriented Business Curriculum to Enhance Graduate Competitiveness in the Global Market - Vicente Pironti; Aytan Azizli; Garima Diwan; Zohaib Hassan Sain (Edu Spectrum: Journal of Multidimensional Education, 2026)
This study examines the development of an industry-oriented business curriculum to enhance graduate competitiveness in the global market. The research employs a qualitative approach using content analysis to evaluate curriculum structures, experiential learning models, digital competency integration, and industry collaboration practices in higher education institutions. The findings reveal that industry-oriented curricula significantly improve graduate employability by aligning academic learning with labor market requirements. Experiential learning methods, including internships, project-based learning, and business simulations, contribute to the development of practical and professional competencies. In addition, collaboration between universities and industries strengthens curriculum relevance and supports innovation in teaching and learning processes. The study also highlights the importance of digital literacy, global perspectives, and communication skills in preparing graduates for international competition. Ultimately, curriculum innovation is essential for producing adaptive, competitive, and professionally prepared graduates capable of responding to rapid economic and technological transformations